Analisis Peran Pemerintah Daerah dalam Memoderasi Faktor Partisipasi, Sosial, Ekonomi, Lingkungan dan Swasta terhadap Kebijakan Pengelolaan Sampah: Analysis of the Role of Local Government in Moderating Participation, Social, Economic, Environmental and Private Sector Factors Influencing Waste Management Policy - Wahyudin Noor; I Nyoman Sudyana; Heriamariaty Heriamariaty; Johanna Maria Rotinsulu (JURNAL HUTAN TROPIKA, 2026)
Waste management is part of the fifth mission of regional development, which emphasizes the importance of environmental conservation as the foundation of sustainable development. The environment is considered an essential component because the impacts of development accumulate over the long term. Development requires the utilization of natural resources, which may generate negative environmental consequences. This study aims to analyze the role of local government in moderating participation, social, economic, environmental and private sector factors influencing waste management policy. A quantitative approach employing Structural Equation Modeling–Partial Least Squares (SEM-PLS) was applied. The results indicate that community participation has a positive and significant effect on waste management policy (β = 0.428; p < 0.001), suggesting that higher community involvement enhances the effectiveness of waste management. Social factors also have a positive and significant influence (β = 0.337; p = 0.001), particularly through mutual cooperation and social support. Economic factors positively and significantly affect waste management policy (β = 0.301; p = 0.001) through economic benefits, waste banks, and recycling activities. Environmental factors exert the strongest influence (β = 0.486; p < 0.001) through increased environmental awareness. The private sector also has a positive and significant effect (β = 0.389; p < 0.001). Furthermore, local government significantly moderates the relationship between all variables and waste management policy (β = 0.514; p < 0.001), thereby strengthening the success of participatory waste management in East Barito Regency.